The flow of love in the poetic voices of Fernanda Laguna and Dalia Rosetti - Julieta Novelli (Estudios de Teoría Literaria, 2024)
The article aims to analyse the ways in which some of the poetic voices of Fernanda Laguna and her heteronym, Dalia Rosetti, enter and leave the lover`s discourse, considering certain Barthesian figures together with areas of literary tradition. Since love is a form of venture, the figures that emerge from it, such as waiting, obsession, identification, suffering, magic and the unspeakable, will be addressed. Within this framework, the condition of the experience of the lover subject will be studied in the plaquettes No quiero manipularte con este cuento (2008) and desearía (2007) signed by Laguna together with the plaquette Hice todo porque me mires (2008) signed by Rosetti. In these poems, the voices in love lose control of themselves and of everyday certainties in order to surrender, instead, to the possibility of deviating and straying both from the known routine and from their own selves.